Bentonite slurry for improving shield cabin soil in water-rich stratum and preparation method of bentonite slurry

By using bentonite slurry made of components such as sodium bentonite in shield tunneling construction in water-rich strata, a complex three-dimensional gel network structure is formed, which solves the problems of large soil permeability coefficient and poor flow plasticity in water-rich strata, and significantly improves Improve the safety and efficiency of construction.

CN119331582APending Publication Date: 2025-01-21STATE GRID JIANGSU ELECTRIC POWER CO LTD NANJING POWER SUPPLY COMPANY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411248168.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In water-rich formations, the soil has a large permeability coefficient, is prone to gushing, has no cohesion, and has poor fluid plasticity, resulting in poor cabin improvement effect during shield construction.

Method used

A bentonite mud including sodium bentonite, silicate, surfactant, water-based polyamide wax and modified starch is used. Through the synergistic effect of these components, a complex three-dimensional gel network structure is formed, which significantly improves the anti-penetration of the mud. properties and rheological properties.

Benefits of technology

The bentonite mud maintains good sealing effect and fluidity under high water pressure and high permeability environments, significantly improves the safety and efficiency of shield tunneling construction, and effectively copes with construction challenges in water-rich strata.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031469920000122
    Figure BDA0005031469920000122
  • Figure BDA0005031469920000131
    Figure BDA0005031469920000131
Patent Text Reader

Abstract

The invention relates to the technical field of shield construction materials, in particular to bentonite slurry for water-rich stratum shield cabin soil improvement and a preparation method of the bentonite slurry, and the bentonite slurry comprises the following components in parts by weight: 8-12 parts of sodium bentonite, 1-3 parts of silicate, 1-3 parts of a surfactant, 0.5-1.5 parts of water-based polyamide wax, 1-3 parts of modified starch and 11-22 parts of water. According to the water-rich stratum shield cabin soil improved bentonite slurry provided by the invention, the mineral material, the water-soluble polymer material and the surfactant are combined, so that the stability, permeability resistance and rheological property of the slurry in a water-rich stratum are remarkably improved. The slurry can effectively cope with high water pressure and high permeability environment, keeps good plugging effect and fluidity, greatly improves the safety and efficiency of shield construction, and provides reliable technical guarantee for tunnel engineering under complex geological conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shield construction materials, and in particular to bentonite slurry used for improving shield cabin soil in water-rich strata and a preparation method thereof. Background Art

[0002] Shield tunnel construction has the advantages of little impact on the surrounding building environment, fast construction speed, high degree of construction automation, and good safety, and is widely used, especially in areas with dense buildings or special strata. Common types of shield machines are earth pressure balance shield machines (EPB shields) and slurry balance shield machines (slurry shields). Among them, EPB shields occupy almost no surface area, have relatively low construction costs, and are widely used in urban subway tunnel construction.

[0003] During the construction of earth pressure shield, due to the complexity and diversity of the strata, problems such as closure of the pressure chamber, cake formation or gushing of the discharge port of the earth discharger are prone to occur. It is necessary to improve the soil in the pressure chamber behind the cutter head to a plastic flow state, that is, higher fluidity, lower permeability, and better compressibility, so as to support the soil and water pressure of the excavation face and maintain the stability of the excavation face. In the process of improving the soil, it is necessary to select appropriate improvers according to the specific stratum conditions. The main improvers include the following: First, mineral improvers. Mainly using bentonite and montmorillonite as the main raw materials, after using pulping equipment to mix them evenly, they are pumped into the excavated soil to ensure the fluidity and impermeability of the soil. Second, water-soluble polymer improvers. During the shield construction process, sodium carboxymethyl cellulose is generally used to increase the viscosity of the soil on the excavation construction surface. Third, interfacial active material improvers, that is, directly injecting foaming agents into the excavated soil to improve the fluidity and impermeability of the soil, which can prevent the soil from adhering during the excavation process. At present, the commonly used cabin soil conditioners at home and abroad include surfactant-based conditioners or mineral-based conditioners. The problem is that, although a single surfactant-based conditioner can improve the fluidity of the cabin soil to a good extent, it is easily squeezed out of the pores of soil particles under the action of water pressure, and the improvement effect on the permeability of the cabin soil is poor; a single mineral-based conditioner can reduce the permeability of the cabin soil to a good extent, but a large amount of injection is required to achieve the ideal effect, which is costly and causes the volume of discharged cabin soil to increase exponentially, making subsequent treatment of the cabin soil difficult.

[0004] Chinese patent 201811464621.X discloses a method for preparing bubble mud for improving the cabin soil of an earth pressure balance shield, comprising the following steps: firstly, preparing the base slurry: mixing the foaming liquid and the slurry evenly: then generating the bubble mud: placing the base slurry in a closed or semi-closed container, stirring the base slurry with a stirrer, and obtaining the bubble mud. The above scheme obtains the bubble mud by mixing the foaming liquid and the bentonite slurry to achieve the effect of improving fluidity, adjusting strength, and reducing permeability coefficient, so as to be used for improving the cabin soil of an earth pressure shield machine. However, when the scheme encounters high water pressure and high permeability water-rich strata, on the one hand, under the high water pressure environment, the bubbles are very easy to compress and rupture, causing the mud to lose its original viscosity and rheological properties. The high permeability strata will accelerate the loss of water in the mud, further destroying the bubble structure, so that the free water in the soil cannot be fully replaced by the foam, and the permeability of the soil cannot be greatly improved; on the other hand, the calcium-based bentonite in the mud has limited expansion capacity under high water pressure and cannot form an effective anti-seepage barrier. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof to solve the problems of large soil permeability, easy gushing, lack of cohesion, poor soil flow plasticity, etc. in water-rich strata, so as to solve the above problems.

[0006] The technical solution of the present invention is implemented as follows: On the one hand, the present invention provides a bentonite mud for improving the soil of a shield cabin in a water-rich stratum, which comprises the following components by weight: 8-12 parts of sodium bentonite, 1-3 parts of silicate, 1-3 parts of surfactant, 0.5-1.5 parts of water-based polyamide wax, 1-3 parts of modified starch, and 11-22 parts of water.

[0007] In the present invention, sodium bentonite is used as the main material of the mud. The sodium bentonite has excellent water absorption and swelling properties and suspension properties. Its unique layered structure can quickly disperse in water and absorb a large amount of water to form a stable gel network, providing the basic viscosity and structural strength of the mud. The non-polar aliphatic hydrocarbon part of the water-based polyamide wax can form a hydrophobic layer on the surface of the bentonite particles. The polar amide functional groups form hydrogen bonds with silicates to fill the gaps in the gel network to form a three-dimensional composite structure. The permeability resistance of the mud is significantly improved through multiple plugging mechanisms, and the water flow in the high-permeability water-rich formation is effectively controlled. At the same time, the structural stability of the mud is enhanced, so that it can still maintain good rheological properties under high water pressure and high shear force environments.

[0008] The hydroxyl groups in the modified starch molecules can form hydrogen bonds with the siloxy groups on the surface of bentonite, strengthening the interaction between the two; at the same time, the long-chain molecules of the modified starch can form bridges between bentonite particles to build a more stable three-dimensional network structure, which can complement the gel network structure, fill each other's gaps, and form a more dense and uniform composite network, thereby improving the internal cohesion of the mud, enabling it to maintain good structural integrity and stability in high water pressure, high permeability, and water-rich strata, thereby improving the safety and efficiency of shield construction. Surfactants can significantly reduce the surface tension of the mud, thereby promoting the uniform dispersion of each component in water.

[0009] On the basis of the above technical solution, preferably, the silicate is sodium silicate and / or magnesium silicate, and the surfactant is one or a mixture of several of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and coconut oil fatty acid diethanolamide.

[0010] On the basis of the above technical solution, preferably, the preparation method of the modified starch comprises the following steps:

[0011] (1) gelatinizing starch to obtain pretreated starch;

[0012] (2) Dissolve sodium dihydrogen phosphate in water, then add sodium hydroxide solution, add pretreated starch and hydroxypropyl guar gum, and stir to react for 1-3 hours; add a cross-linking agent, react at a constant temperature of 45-60° C. for 1-3 hours, wash with water, centrifuge, and dry to obtain modified starch.

[0013] Based on the above technical solution, preferably, the gelatinization treatment in step (1) specifically includes:

[0014] (1.1) Mix starch, sodium hypochlorite and water, then add nickel sulfate solution, stir at room temperature, and allow to oxidize for 10-14 hours to obtain oxidized starch;

[0015] (1.2) Mix the oxidized starch obtained in step (1.1) with water, add sodium hydroxide solution, and stir at room temperature for 15-25 minutes to obtain pretreated starch.

[0016] Specifically, sodium hypochlorite is used as an oxidant, and under the catalysis of nickel sulfate, the hydroxyl groups in the starch molecules are selectively oxidized to improve the hydrophilicity and reactivity of the starch; then the gelatinization treatment is carried out to cause the starch to expose more reaction sites and increase the solubility and dispersibility of the starch. Phosphate groups and hydroxypropyl guar gum are introduced through phosphorylation reaction and grafting respectively, in which the negatively charged phosphate groups can produce electrostatic interactions with the positively charged sites on the surface of bentonite, enhance the binding of modified starch and bentonite, help to form a more stable gel network structure, and improve the overall stability of the mud; at the same time, phosphorylation treatment can improve the heat resistance of starch and keep it stable under high temperature environment. The introduction of hydroxypropyl guar gum forms long-chain branches on the starch main chain, resulting in increased intermolecular entanglement, thereby increasing the viscosity of the solution; the long chain of hydroxypropyl guar gum forms a physical bridge between the bentonite layers, further strengthening the stability of the network structure; hydroxypropyl guar gum has a strong water retention capacity, and its introduction can increase the water retention of modified starch. The dense network structure formed by modified starch and bentonite significantly improves the anti-penetration ability of the mud.

[0017] On the basis of the above technical scheme, preferably, in step (1.1), the added mass ratio of starch, sodium hypochlorite and nickel sulfate is 1:0.1-0.2:0.02-0.03, the mass fraction of the nickel sulfate solution is 0.3-0.7%, and the starch is a mixture of one or more of corn starch, potato starch and wheat starch.

[0018] On the basis of the above technical solution, preferably, in step (1.2), the mass ratio of the oxidized starch to sodium hydroxide is 1:0.08-0.12, and the mass fraction of the sodium hydroxide solution is 8-12%.

[0019] On the basis of the above technical scheme, preferably, in step (2), the mass ratio of pretreated starch, hydroxypropyl guar gum, cross-linking agent and sodium dihydrogen phosphate is 1:0.5-0.75:0.15-2.5:0.1-0.2, and the amount of sodium hydroxide solution added is 0.8-1.2 mol / L.

[0020] On the basis of the above technical solution, preferably, in step (2), the cross-linking agent is any one of ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether or epichlorohydrin.

[0021] On the other hand, the present invention provides a method for preparing bentonite slurry for improving shield cabin soil in water-rich strata, comprising the following steps:

[0022] S1. Mix sodium bentonite, water and silicate, and stir to obtain component A;

[0023] S2, mixing the surfactant, modified starch and water-based polyamide wax, stirring to obtain component B;

[0024] S3. Store component A and component B separately.

[0025] On the basis of the above technical scheme, preferably, during use, component A and component B are injected into the cabin soil in proportion to improve the cabin soil, the total mass of component A and component B accounts for 25-35% of the cabin soil mass, and the injection ratio of component A to component B is 10-12:4.

[0026] Beneficial effects of the present invention:

[0027] (1) The improved bentonite mud for shield cabin soil in water-rich strata provided by the present invention significantly improves the stability, anti-permeability and rheological properties of the mud in water-rich strata by combining mineral materials, modified starch and surfactants. The mud can effectively cope with high water pressure and high permeability environments, maintain good sealing effect and fluidity, greatly improve the safety and efficiency of shield construction, and provide reliable technical guarantees for tunnel engineering under complex geological conditions;

[0028] (2) Starch is modified by oxidation, gelatinization, phosphorylation, grafting and cross-linking to introduce phosphate groups and hydroxypropyl guar gum. The modified starch network structure contains a large number of hydroxyl, carboxyl and phosphate groups, which can form hydrogen bonds with the layered structure of sodium bentonite to enhance the overall stability of the mud. The long-chain molecules of the modified starch can entangle with the hydrophobic segments of the water-based polyamide wax to enhance the lubricity and shear resistance of the mud. In addition, the porous nature of the modified starch network structure can also adsorb and encapsulate other additives in the mud, such as surfactants, to form a highly integrated composite system. This multiple synergistic effect not only significantly improves the viscosity, yield value and permeability resistance of the mud, but also maintains good fluidity and shear stability, greatly improving the comprehensive performance of the mud in water-rich formations.

[0029] The coordinated use of sodium bentonite, water-based polyamide wax and silicate forms a complex three-dimensional gel network structure, in which the layered structure of sodium bentonite forms the basic network skeleton; the long-chain molecules of water-based polyamide wax are interspersed in it, enhancing the flexibility and lubricity of the network; and the silicate forms silicon-oxygen cross-linking at the network nodes to further strengthen the overall structure. This multi-cross-linked network not only improves the viscosity and yield value of the mud, but also significantly enhances its anti-permeability and plugging effect. At the same time, this network structure has good recoverability, can be temporarily destroyed under the action of shear force, and can be quickly rebuilt after the action stops, giving the mud excellent thixotropy and rheological properties. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available.

[0032] Sodium bentonite was purchased from Sishui County Hengjian Bentonite Co., Ltd., 450 mesh;

[0033] Water-based polyamide wax was purchased from Tianjin Ruike Chemical Trading Co., Ltd. with a purity of 20%;

[0034] Starch is potato starch, purchased from Nanjing Chemical Reagent Co., Ltd., with an active ingredient content of 99%;

[0035] Hydroxypropyl guar gum was purchased from Renqiu Pengyu Chemical Co., Ltd. with a viscosity of 0.8 cps.

[0036] The experimental cabin soil used in the following embodiments and comparative examples is mainly composed of sandstone and limestone, with a particle size composition of: about 20% for 2-20 mm, about 35% for 20-60 mm, and about 35% for larger than 60 mm; the rest is miscellaneous sand, gravel sand and silty clay filling, with a moisture content of 25%.

[0037] Example 1

[0038] This embodiment provides a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof, comprising the following components: 10 g of sodium bentonite, 2 g of sodium silicate, 2 g of sodium dodecylbenzene sulfonate, 1 g of water-based polyamide wax, 2 g of modified starch, and 17 g of water;

[0039] The preparation method of the bentonite slurry is as follows:

[0040] S1. Mix 10 g of sodium bentonite, 2 g of sodium silicate and 12 g of water, and stir at 550 rpm for 20 min to obtain component A;

[0041] S2, 2 g of sodium dodecylbenzene sulfonate, 2 g of modified starch, 1 g of water-based polyamide wax and 5 g of water were mixed, and stirred at a speed of 450 rpm for 15 min to obtain component B;

[0042] S3. Store component A and component B separately.

[0043] Component A, component B and cabin soil are mixed in proportion to obtain improved cabin soil A, wherein the mass ratio of component A to component B is 11:4, and the total mass of component A and component B accounts for 30% of the mass of the cabin soil.

[0044] Wherein, the preparation method of modified starch is as follows:

[0045] (1) 10 g of starch, 1.5 g of sodium hypochlorite and 12 mL of water were mixed and stirred for 5 min, 0.25 g of nickel sulfate was mixed with water to prepare a nickel sulfate solution with a mass percentage of 0.5%, the nickel sulfate solution was added to the above mixed solution, stirred at room temperature (25-30° C.) for 30 min, and then allowed to stand for oxidation for 12 h to obtain oxidized starch; 10 g of oxidized starch was mixed with 10 mL of water and stirred for 5 min, 1.0 g of sodium hydroxide was prepared into a sodium hydroxide solution with a mass percentage of 10%, the sodium hydroxide solution was added to the oxidized starch solution, and stirred at 65° C. at a speed of 500 rpm for 20 min for gelatinization treatment to obtain pretreated starch;

[0046] (2) 1.5 g of sodium dihydrogen phosphate was dissolved in 25 mL of water, and then 1 mol / L of sodium hydroxide solution was added, followed by 10 g of pretreated starch and 6.5 g of hydroxypropyl guar gum, and the mixture was stirred and reacted at room temperature (25-30° C.) for 2 h; 2 g of ethylene glycol diglycidyl ether was added, and the mixture was reacted at 55° C. for 2 h, and the mixture was washed with water three times, each time using 50 mL of deionized water, and centrifuged at 4000 rpm for 15 min, and dried in an oven at 60° C. for 8 h to obtain modified starch.

[0047] Example 2

[0048] This embodiment provides a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof, comprising the following components: 8g of sodium-based bentonite, 1g of sodium silicate, 1g of sodium dodecyl sulfate, 0.5g of water-based polyamide wax, 1g of modified starch, and 11g of water;

[0049] The preparation method of the bentonite slurry is as follows:

[0050] S1, 8 g of sodium bentonite, 1 g of magnesium silicate and 9 g of water were mixed, and stirred at a speed of 500 rpm for 15 min to obtain component A;

[0051] S2, 1 g of sodium dodecylbenzene sulfonate, 1 g of modified starch, 0.5 g of water-based polyamide wax and 2 g of water were mixed, and stirred at a speed of 400 rpm for 10 min to obtain component B;

[0052] S3. Store component A and component B separately.

[0053] Component A, component B and cabin soil are mixed in proportion to obtain improved cabin soil B, wherein the mass ratio of component A to component B is 10:4, and the total mass of component A and component B accounts for 25% of the mass of the cabin soil.

[0054] Wherein, the preparation method of modified starch is as follows:

[0055] (1) 10 g of starch, 1 g of sodium hypochlorite and 11 mL of water were mixed and stirred for 5 min, 0.2 g of nickel sulfate was mixed with water to prepare a nickel sulfate solution with a mass percentage of 0.3%, the nickel sulfate solution was added to the above mixed solution, stirred at room temperature (25-30° C.) for 30 min, and then allowed to stand for oxidation for 10 h to obtain oxidized starch; 10 g of oxidized starch was mixed with 10 mL of water and stirred for 5 min, 0.8 g of sodium hydroxide was prepared into a sodium hydroxide solution with a mass percentage of 8%, the sodium hydroxide solution was added to the oxidized starch solution, and stirred at 60° C. at a speed of 500 rpm for 20 min for gelatinization treatment to obtain pretreated starch;

[0056] (2) 1.13 g of sodium dihydrogen phosphate was dissolved in 20 mL of water, and then 0.8 mol / L of sodium hydroxide solution was added, followed by 10 g of pretreated starch and 5 g of hydroxypropyl guar gum, and the mixture was stirred and reacted at room temperature (25-30° C.) for 1 h; 1.5 g of neopentyl glycol diglycidyl ether was added, and the mixture was reacted at a constant temperature of 45° C. for 1 h, and the mixture was washed with water 3 times, each time using 50 mL of deionized water, and centrifuged at 3500 rpm for 10 min, and dried in an oven at 60° C. for 6 h to obtain modified starch.

[0057] Example 3

[0058] The present embodiment provides a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof, comprising the following components: 12 g of sodium bentonite, 3 g of sodium silicate, 3 g of coconut oil fatty acid diethanolamide, 1.5 g of water-based polyamide wax, 3 g of modified starch, and 22 g of water;

[0059] The preparation method of the bentonite slurry is as follows:

[0060] S1. Mix 12 g of sodium bentonite, 3 g of sodium silicate and 15 g of water, and stir at 600 rpm for 20 min to obtain component A;

[0061] S2, 3 g of sodium dodecylbenzene sulfonate, 3 g of modified starch, 1.5 g of water-based polyamide wax and 7 g of water were mixed, and stirred at a speed of 500 rpm for 15 min to obtain component B;

[0062] S3. Store component A and component B separately.

[0063] Component A, component B and cabin soil are mixed in proportion to obtain improved cabin soil C, wherein the mass ratio of component A to component B is 12:4, and the total mass of component A and component B accounts for 35% of the mass of the cabin soil.

[0064] Wherein, the preparation method of modified starch is as follows:

[0065] (1) 10 g starch, 2 g sodium hypochlorite and 12 mL water were mixed and stirred for 5 min, 0.3 g nickel sulfate was prepared with water to prepare a nickel sulfate solution with a mass percentage of 0.7%, the nickel sulfate solution was added to the above mixed solution, stirred at room temperature (25-30° C.) for 30 min, and then allowed to stand for oxidation for 14 h to obtain oxidized starch; 10 g oxidized starch was mixed with 10 mL water and stirred for 5 min, 1.2 g sodium hydroxide was prepared to prepare a sodium hydroxide solution with a mass percentage of 12%, the sodium hydroxide solution was added to the oxidized starch solution, and stirred at 70° C. at a speed of 500 rpm for 20 min for gelatinization treatment to obtain pretreated starch;

[0066] (2) 1.88 g of sodium dihydrogen phosphate was dissolved in 30 mL of water, and then a 1.2 mol / L sodium hydroxide solution was added, followed by 10 g of pretreated starch and 7.5 g of hydroxypropyl guar gum, and the mixture was stirred and reacted at room temperature (25-30° C.) for 3 h; 2.5 g of ethylene glycol diglycidyl ether was added, and the mixture was reacted at a constant temperature of 60° C. for 3 h, and the mixture was washed with water for 3 times, each time using 50 mL of deionized water, and centrifuged at 4500 rpm for 20 min, and dried in an oven at 60° C. for 10 h to obtain modified starch.

[0067] Example 4

[0068] The present embodiment provides a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof, comprising the following components: 9 g of sodium bentonite, 2.5 g of sodium silicate, 1.5 g of sodium dodecylbenzene sulfonate, 1.5 g of coconut oil fatty acid diethanolamide, 0.8 g of water-based polyamide wax, 2.5 g of modified starch, and 20 g of water;

[0069] The preparation method of the bentonite slurry is as follows:

[0070] S1, 9 g of sodium bentonite, 2.5 g of sodium silicate and 12 g of water were mixed, and stirred at a speed of 500 rpm for 25 min to obtain component A;

[0071] S2, 1.5 g of sodium dodecylbenzene sulfonate, 1.5 g of coconut oil fatty acid diethanolamide, 2.5 g of modified starch, 0.8 g of water-based polyamide wax and 8 g of water were mixed, and stirred at a speed of 500 rpm for 10 min to obtain component B;

[0072] S3. Store component A and component B separately.

[0073] Component A, component B and cabin soil are mixed in proportion to obtain improved cabin soil D, wherein the mass ratio of component A to component B is 10:4, and the total mass of component A and component B accounts for 32% of the mass of the cabin soil.

[0074] Wherein, the preparation method of modified starch is as follows:

[0075] (1) 10 g starch, 1.2 g sodium hypochlorite and 12 mL water were mixed and stirred for 5 min, 0.25 g nickel sulfate was prepared with water to prepare a nickel sulfate solution with a mass percentage of 0.4%, the nickel sulfate solution was added to the mixed solution, stirred at room temperature (25-30° C.) for 30 min, and then allowed to stand for oxidation for 13 h to obtain oxidized starch; 10 g oxidized starch was mixed with 10 mL water and stirred for 5 min, 0.9 g sodium hydroxide was prepared to prepare a sodium hydroxide solution with a mass percentage of 11%, the sodium hydroxide solution was added to the oxidized starch solution, and stirred at 70° C. at a speed of 500 rpm for 20 min for gelatinization to obtain pretreated starch;

[0076] (2) 1.7 g of sodium dihydrogen phosphate was dissolved in 30 mL of water, and then a 1.1 mol / L sodium hydroxide solution was added, followed by 10 g of pretreated starch and 5.5 g of hydroxypropyl guar gum, and the mixture was stirred and reacted at room temperature (25-30° C.) for 1.5 h; 2.5 g of ethylene glycol diglycidyl ether was added, and the mixture was reacted at a constant temperature of 45° C. for 2.5 h, and the mixture was washed with water three times, each time using 50 mL of deionized water, and centrifuged at 4000 rpm for 15 min, and dried in an oven at 60° C. for 8 h to obtain modified starch.

[0077] Comparative Example 1

[0078] This embodiment provides a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof, comprising the following components: 10 g of sodium bentonite, 2 g of sodium silicate, 2 g of sodium dodecylbenzene sulfonate, 1 g of water-based polyamide wax, 2 g of starch, and 17 g of water;

[0079] The preparation method of the bentonite slurry is as follows:

[0080] S1. Mix 10 g of sodium bentonite, 2 g of sodium silicate and 12 g of water, and stir at 550 rpm for 20 min to obtain component A;

[0081] S2, 2 g of sodium dodecylbenzene sulfonate, 2 g of starch, 1 g of water-based polyamide wax and 5 g of water were mixed, and stirred at a speed of 450 rpm for 15 min to obtain component B;

[0082] S3. Store component A and component B separately.

[0083] Component A, component B and cabin soil are mixed in proportion to obtain improved cabin soil E-1, wherein the mass ratio of component A to component B is 11:4, and the total mass of component A and component B accounts for 30% of the mass of the cabin soil.

[0084] Comparative Example 2

[0085] This embodiment provides a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof, comprising the following components: 10 g of sodium bentonite, 2 g of sodium silicate, 2 g of sodium dodecylbenzene sulfonate, 1 g of water-based polyamide wax, 2 g of modified starch, and 17 g of water;

[0086] The preparation method of the bentonite slurry is as follows:

[0087] S1. Mix 10 g of sodium bentonite, 2 g of sodium silicate and 12 g of water, and stir at 550 rpm for 20 min to obtain component A;

[0088] S2, 2 g of sodium dodecylbenzene sulfonate, 2 g of modified starch, 1 g of water-based polyamide wax and 5 g of water were mixed, and stirred at a speed of 450 rpm for 15 min to obtain component B;

[0089] S3. Store component A and component B separately.

[0090] Component A, component B and cabin soil are mixed in proportion to obtain improved cabin soil E-2, wherein the mass ratio of component A to component B is 11:4, and the total mass of component A and component B accounts for 30% of the mass of the cabin soil.

[0091] Wherein, the preparation method of modified starch is as follows:

[0092] (1) 10 g of starch, 1.5 g of sodium hypochlorite and 12 mL of water were mixed and stirred for 5 min, 0.25 g of nickel sulfate was prepared with water to form a nickel sulfate solution with a mass percentage of 0.5%, the nickel sulfate solution was added to the above mixed solution, stirred at room temperature (25-30° C.) for 30 min, and then allowed to stand for oxidation for 12 h to obtain oxidized starch; 10 g of oxidized starch was mixed with 10 mL of water and stirred for 5 min, 1.0 g of sodium hydroxide was prepared to form a sodium hydroxide solution with a mass percentage of 10%, the sodium hydroxide solution was added to the oxidized starch solution, and stirred at 65° C. at a speed of 500 rpm for 20 min for gelatinization to obtain modified starch.

[0093] Comparative Example 3

[0094] This embodiment provides a bentonite slurry for improving shield cabin soil in water-rich strata and a preparation method thereof, comprising the following components: 10 g of sodium-based bentonite, 2 g of sodium silicate, 2 g of modified starch, and 17 g of water;

[0095] The preparation method of the bentonite slurry is as follows:

[0096] S1. Mix 10 g of sodium bentonite, 2 g of sodium silicate and 12 g of water, and stir at 550 rpm for 20 min to obtain component A;

[0097] S2, 2 g of modified starch and 5 g of water were mixed, and stirred at a speed of 450 rpm for 15 min to obtain component B;

[0098] S3. Store component A and component B separately.

[0099] Component A, component B and cabin soil are mixed in proportion to obtain improved cabin soil E-3, wherein the mass ratio of component A to component B is 11:4, and the total mass of component A and component B accounts for 30% of the mass of the cabin soil.

[0100] Wherein, the preparation method of modified starch is as follows:

[0101] (1) 10 g of starch, 1.5 g of sodium hypochlorite and 12 mL of water were mixed and stirred for 5 min, 0.25 g of nickel sulfate was mixed with water to prepare a nickel sulfate solution with a mass percentage of 0.5%, the nickel sulfate solution was added to the above mixed solution, stirred at room temperature (25-30° C.) for 30 min, and then allowed to stand for oxidation for 12 h to obtain oxidized starch; 10 g of oxidized starch was mixed with 10 mL of water and stirred for 5 min, 1.0 g of sodium hydroxide was prepared into a sodium hydroxide solution with a mass percentage of 10%, the sodium hydroxide solution was added to the oxidized starch solution, and stirred at 65° C. at a speed of 500 rpm for 20 min for gelatinization treatment to obtain pretreated starch;

[0102] (2) 1.5 g of sodium dihydrogen phosphate was dissolved in 15 mL of water, and then 1 mol / L of sodium hydroxide solution was added, followed by 10 g of pretreated starch and 6.5 g of hydroxypropyl guar gum, and the mixture was stirred and reacted at room temperature (25-30° C.) for 2 h; 2 g of ethylene glycol diglycidyl ether was added, and the mixture was reacted at 55° C. for 2 h, and the mixture was washed with water for 3 times, each time using 50 mL of deionized water, and centrifuged at 4000 rpm for 15 min, and dried in an oven at 60° C. for 8 h to obtain modified starch.

[0103] Performance Testing

[0104] The viscosity of the bentonite slurries prepared in Examples 1-4 and Comparative Examples 1-3 was tested using a NXS-11A rotational viscometer produced by Chengdu Instrument Factory. An appropriate amount of sample was taken in a specific container and tested according to the NXS-11A rotational viscometer test process.

[0105] The permeability coefficient and slump of the improved cabin soil prepared in Examples 1-4 and Comparative Examples 1-3 were tested, and the results are shown in Table 1.

[0106] (1) Permeability coefficient test: During the test, the filter layer and the improved cabin soil layer are placed in the sample cylinder in turn, and water is added to the sample cylinder until water flows out of the upper outlet. After closing the lower outlet and the middle outlet, the piston is pressed in and pressurized to the initial water head height of the formation. The lower outlet is opened, and the volume V of the water flowing out within the time t is measured to measure the permeability coefficient. The common burial depth of the shield is 10-20m, so the permeability test pressure is 0.1MPa-0.2MPa. The formula for calculating the permeability coefficient is: Where: V is the permeation flow rate; A is the cross-sectional area of ​​the permeation column; H is the permeation head. Since the water height in the device is very small compared to the external air pressure, it can be ignored, so the air pressure value is taken as the total head value; t is the permeation time; L is the length of the permeation path. The permeability coefficient must be less than 10 -5 cm / s.

[0107] (2) Slump test: Use a standard mortar slump bucket with an upper diameter of 50 mm, a lower diameter of 100 mm, and a height of 150 mm. Put the improved cabin soil into the slump bucket, tamp it tightly, and then gently lift the slump bucket upwards to allow the test block to collapse and deform under the action of gravity. The distance the top drops is recorded as the slump. The slump of the soil between 100-150 mm meets the requirements of soil improvement. The larger the value, the better the rheology. The test results are shown in Table 1.

[0108] Table 1 Performance test results

[0109]

[0110]

[0111] As shown in Table 1, by comparing the examples with the comparative examples, the bentonite slurry prepared in Examples 1-4 of the present invention has higher viscosity, higher slump and smaller permeability coefficient; it can be used in the improvement of the water-rich bottom shield cabin soil to reduce the cabin soil permeability coefficient, improve its anti-permeability, and thus curb the occurrence of gushing; at the same time, according to the slump test results, it can be obtained that the bentonite slurry prepared by the present invention has better rheological properties. The starch in Comparative Example 1 is not modified, the modified starch in Comparative Example 2 has not undergone phosphorylation, grafting and cross-linking steps, and no surfactant and water-based polyamide wax are added to the formula in Comparative Example 3, and the effects are not as good as those of Examples 1-4.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A bentonite slurry for improving shield cabin soil in water-rich strata, characterized in that: The bentonite slurry comprises the following components by weight: 8-12 parts of sodium bentonite, 1-3 parts of silicate, 1-3 parts of surfactant, 0.5-1.5 parts of water-based polyamide wax, 1-3 parts of modified starch, and 11-22 parts of water.

2. The bentonite slurry for improving shield cabin soil in water-rich strata according to claim 1, characterized in that: The silicate is sodium silicate and / or magnesium silicate, and the surfactant is one or a mixture of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and coconut oil fatty acid diethanolamide.

3. The bentonite slurry for improving shield cabin soil in water-rich strata according to claim 1, characterized in that: The preparation method of the modified starch comprises the following steps: (1) gelatinizing starch to obtain pretreated starch; (2) Dissolve sodium dihydrogen phosphate in water, then add sodium hydroxide solution, add pretreated starch and hydroxypropyl guar gum, and stir to react for 1-3 hours; add a cross-linking agent, react at a constant temperature of 45-60° C. for 1-3 hours, wash with water, centrifuge, and dry to obtain modified starch.

4. The bentonite slurry for improving shield cabin soil in water-rich strata according to claim 3, characterized in that: Step (1) specifically includes: (1.1) Mix starch, sodium hypochlorite and water, then add nickel sulfate solution, stir at room temperature, and allow to oxidize for 10-14 hours to obtain oxidized starch; (1.2) Mix the oxidized starch obtained in step (1.1) with water, add sodium hydroxide solution, and stir at 60-70° C. for 15-25 minutes to obtain pretreated starch.

5. The bentonite slurry for improving shield cabin soil in water-rich strata according to claim 4, characterized in that: In step (1.1), the mass ratio of starch, sodium hypochlorite and nickel sulfate is 1:0.1-0.2:0.02-0.03, the mass fraction of the nickel sulfate solution is 0.3-0.7%, and the starch is a mixture of one or more of corn starch, potato starch and wheat starch.

6. The bentonite slurry for improving shield cabin soil in water-rich strata according to claim 4, characterized in that: In step (1.2), the mass ratio of the oxidized starch to sodium hydroxide is 1:0.08-0.12, and the mass fraction of the sodium hydroxide solution is 8-12%.

7. The bentonite slurry for improving shield cabin soil in water-rich strata according to claim 3, characterized in that: In step (2), the mass ratio of pretreated starch, hydroxypropyl guar gum, cross-linking agent and sodium dihydrogen phosphate is 1:0.5-0.75:0.15-2.5:0.1-0.2, and the amount of sodium hydroxide solution added is 0.8-1.2 mol / L.

8. The bentonite slurry for improving shield cabin soil in water-rich strata according to claim 3, characterized in that: In step (2), the cross-linking agent is any one of ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether or epichlorohydrin.

9. A method for preparing bentonite slurry for improving shield cabin soil in water-rich strata according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix sodium bentonite, water and silicate, and stir to obtain component A; S2, mixing the surfactant, modified starch and water-based polyamide wax, stirring to obtain component B; S3. Store component A and component B separately.

10. The method for preparing bentonite slurry for improving shield cabin soil in water-rich strata according to claim 9, characterized in that: When in use, component A and component B are injected into the cabin soil in proportion to improve the cabin soil. The total mass of component A and component B accounts for 25-35% of the cabin soil mass, and the injection ratio of component A to component B is 10-12:4.

Citation Information

Patent Citations

  • A method for preparing bubble-filled slurry for soil improvement in earth pressure balance shield tunneling chambers

    CN109439297B